Analisis Persepsi Masyarakat terhadap Dampak pada Proyek Pembangunan Gedung Trans Studio Mall Kota Banda Aceh terhadap Lingkungan - Aldina Fatimah; Betta Justi Randa (VOCATECH: Vocational Education and Technology Journal, 2021)
AbstractThe planning for the development of the Trans Studio Mall must be carried out wisely by implementing the principles of sustainable and environmentally sound development. This is because the rapid development activities that occur in Indonesia have the potential to put pressure on environmental sustainability. The purpose of this study was to determine the impact of the Trans Studio Mall building project in Banda Aceh City and to determine the fulfillment of environmental eligibility criteria in accordance with the minister of environment regulation. In this study, there were 6 variables on environmental impact criteria and 7 seven variables for the criteria for the suitability of minister of environment Regulation No. 16 of 2012. The data collection technique used a questionnaire by distributing it to 100 respondents with the question criteria of environmental impact and 25 respondents for the minister of environment question criteria. The sampling technique used in this research is purposive sampling.The research method used is descriptive analysis, validity test and reliability test. The results of the validity test of the calculated r value (0.789) meet the requirements with r table (0.195). The results of the reliability test of Cronbach's Alpha value show that the factor on Environmental Impact values Cronbach Alpha (0.855) 0.6, on the minister of environment value Cronbach Alpha factor (0.937) 0.6. The results of the descriptive analysis of the recapitulation of the mean value of the Environmental Impact factor with the answers of 100 respondents showed an average value of 3.95. This shows that development has an impact on the surrounding environment, especially on the X2 indicator of pollution/air pollution with a mean value of 4.01. On the minister of environment factor with the results of the answers, 25 respondents showed an average value of 3.48. This shows that the development is in accordance with the surrounding environment, especially on the X1 indicator of the suitability of the entire preparation process with a mean value of 3.84. Therefore, it can be concluded that the implementation of the construction project has quite an impact on the surrounding environment and this impact can be minimized if the implementation in the field is in accordance with the environmental government regulation number 16 of 2012. Keywords:Environmental impact, Construction project__________________________ AbstrakPerencanaan pembangunan Trans Studio Mall (TSM) harus dilakukan secara arif dengan melaksanakan prinsip pembangunan yang berkelanjutan dan berwawasan lingkungan. Hal ini dikarenakan pesatnya kegiatan pembangunan yang terjadi di Indonesia berpotensi memberikan dampak terhadap kelestarian lingkungan sekitar. Tujuan penelitian ini adalah mengetahui dampak dari proyek pembangunan gedung Trans Studio Mall Kota Banda Aceh dan mengetahui pemenuhan kriteria kelayakan lingkungan sesuai dengan Permen Lingkungan Hidup (LH). Pada penelitian ini terdapat 6 variabel pada kriteria dampak lingkungan dan 7 tujuh variabel untuk kriteria kesesuaian permen LH No 16 tahun 2012. Teknik pengumpulan data menggunakan kuesioner dengan cara membagikan kepada 100 responden dengan kriteria pertanyaan dari dampak lingkungan dan 25 responden untuk kriteria pertanyaan Permen LH. Teknik sampling yang digunakan dalam penelitian ini adalah Purposive Sampling. Metode penelitian yang digunakan adalah analisis derkriptif, uji validitas dan uji reliabilitas. Hasil uji validitas nilai r hitung (0,789) memenuhi syarat dengan r tabel (0,195). Hasil uji reliabilitas nilai Cronbach’s Alpha menunjukkan bahwa faktor pada Dampak Lingkungan nilai Cronbach Alpha (0,855) 0,6, pada faktor Permen LH Cronbach Alpha (0,937) 0,6. Hasil analisis deskriptif rekapitulasi nilai mean faktor Dampak Lingkungan dengan hasil jawaban 100 responden menunjukkan nilai rata-rata 3,95. Hal ini menunjukan bahwa pembangunan berdampak terhadap lingkungan sekitar terutama pada indikator X2 pencemaran/polusi udara dengan nilai mean 4,01. Pada faktor Permen LH dengan hasil jawaban 25 responden menunjukkan nilai rata-rata 3,48. Hal ini menunjukan bahwa pembangunan sesuai terhadap lingkungan sekitar terutama pada indikator X1 kesesuaian keseluruhan proses penyusunan dengan nilai mean 3,84. Oleh karena itu dapat disimpulkan bahwa pelaksanaan proyek konstruksi tsb cukup berdampak bagi lingkungan sekitar dan dampak tersebut dapat di minimalisir jika pelaksanaan dilapangan sesuai dengan peraturan pemerintah lingkungan hidup nomor 16 tahun 2012. Kata Kunci:Dampak lingkungan, Proyek Konstruksi__________________________